Metagenomic Profiling and Microbial Metabolic Potential of Perdido Fold Belt (NW) and Campeche Knolls (SE) in the Gulf of Mexico - Raggi, Luciana; García-Guevara, Fernando; Godoy-Lozano, E. Ernestina; Martínez-Santana, Adrian; Escobar-Zepeda, Alejandra; Gutierrez-Rios, Rosa María; Loza, Antonio; Merino, Enrique; Sanchez-Flores, Alejandro; Licea-Navarro, Alexei; Pardo-Lopez, Liliana; Segovia, Lorenzo; et al. (Frontiers in Microbiology, 2020)
The Gulf of Mexico (GoM) is a particular environment that is continuously exposed to hydrocarbon compounds that may influence the microbial community composition. We carried out a metagenomic assessment of the bacterial community to get an overall view of this geographical zone. We analyzed both taxonomic and metabolic markers profiles to explain how the indigenous GoM microorganims participate in the biogeochemical cycling. Two geographically distant regions in the GoM, one in the north-west (NW) and one in the south-east (SE) of the GoM were analyzed and showed differences in their microbial composition and metabolic potential. These differences provide evidence the delicate equilibrium that sustains microbial communities and biogeochemical cycles. Based on the taxonomy and gene groups, the NW are more oxic sediments than SE ones, which have anaerobic conditions. Both water and sediments show the expected sulfur, nitrogen, and hydrocarbon metabolism genes, with particularly high diversity of the hydrocarbon-degrading ones. Accordingly, many of the assigned genera were associated with hydrocarbon degradation processes, Nitrospira and Sva0081 were the most abundant in sediments, while Vibrio, Alteromonas and Alcanivorax were mostly detected in water samples. This basal-state analysis presents the GoM as a potential source of aerobic and anaerobic hydrocarbon degradation genes important for the ecological dynamics of hydrocarbons and the potential use for water and sediment bioremediation processes.